2006
DOI: 10.1111/j.1527-5299.2006.05595.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Biomarkers in Heart Failure

Abstract: Multiple lines of evidence support the “cytokine hypothesis,” which suggests that inflammation plays an important role in the development and progression of heart failure. Circulating markers of inflammation, such as tumor necrosis factor α, interleukin 6, and C‐reactive protein, may be useful in establishing the diagnosis, gauging prognosis, and evaluating the response to therapy in patients with heart failure. In addition to their potential as heart failure biomarkers, inflammatory cytokines have been invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 43 publications
2
46
0
5
Order By: Relevance
“…Many studies have shown that factors such as the inflammatory status, poor nutritional state and, obviously, the extent of cardiac dysfunction herald a poor prognosis in CHF [7][8][9][10][11][12][13]. However, none of these conventional indicators and, interestingly, also not LVF or RVF, carried any prognostic potential in our patient group.…”
Section: Discussionmentioning
confidence: 58%
“…Many studies have shown that factors such as the inflammatory status, poor nutritional state and, obviously, the extent of cardiac dysfunction herald a poor prognosis in CHF [7][8][9][10][11][12][13]. However, none of these conventional indicators and, interestingly, also not LVF or RVF, carried any prognostic potential in our patient group.…”
Section: Discussionmentioning
confidence: 58%
“…These mediators are involved in, but not limited to, recruiting cells to inflammatory sites and stimulating cell division, proliferation, and differentiation [1]. Increased circulating and intracardiac levels of proinflammatory cytokines have been associated with chronic heart failure [2][3][4][5]. In addition, coronary artery disease (CAD) and dilated cardiomyopathy (DCM), the most common causes of chronic heart failure, are believed to be of an inflammatory origin.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated plasma levels of C-reactive protein (CRP) have been observed and are predictive of poor outcomes in patients with cardiovascular diseases, including CHF; 5 however, CRP has other specific functions, such as amplifying the production of monocyte proinflammatory cytokines such as TNF-α and IL-6, [6][7][8][9][10][11][12] thus suggesting that CRP may not be simply a biomarker, but may play a significant role in the pathogenesis and development of CHF.…”
Section: Editorial P 622mentioning
confidence: 99%